Humanistic curriculum implementation evaluation of MRSM Ulul Albab programme - Abdul Manaf, Umi Kalthom; Abd Rahman, Fadzilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
A drastic movement made by the Majlis Amanah Rakyat (MARA) through its subsidiary, MARA Junior Science College (MRSM) back in 2008 had made a combined scientific and Quranik-based programme possible; The Ulul Albab Programme. An existing MRSM (MRSM Kota Putra) was upgraded to become the MRSM Ulul Albab. The programme was first implemented in 2008. The same Ulul Albab Programme was carried out by Imtiaz, a private school conceptualised by Idris Jusoh, the then Minister of Education, in Kuala Besut Terengganu way back in 1996. Fundamentally, Ulul Alab Porgramme comprises of three major components which are Quranik, Insiklopedik, and Ijtihadik. Ideally, the Ulul Albab Programme is set to produce professional experts, entrepreneurs and technocrats that are well versed in Quran and portraying as well as practicing the values of Islam. Throughout the years of implementation, several positive outcome-based indicators from the Ulul Albab programme immerged at Imtiaz. Hence, the same outcome-based indicators are also expected from MRSM Ulul Albab Kota Putra. However, the outcome-based indicators were incapable of evaluating the sahsiah and ijtihadik components fairly. Therefore, a much more complex curriculum implementation evaluation initiative through students’ and teachers’ experiences are very much needed in order to holistically understand and evaluate the success of Ulul Albab program implementation at MRSM Kota Putra. This paper discusses; (1) The problems faced in evaluating the Ulul Albab curriculum implementation, (2) Conceptualising of a proper model, of which Stake’s Responsive Evaluation for the evaluation of Ulul Albab’s curriculum implementation, and (3) Conceptualising a theoretical framework for the evaluation of Ulul Albab’s curriculum implementation.